"I'm so weak I feel paralyzed. Can you help me?" A case on thyrotoxic periodic paralysis. Issue 6 (29th December 2021) - Mehrdad, Alaie; Jasicki, Stanton; Chheda, Somil
Abstract: Thyrotoxic periodic paralysis (PP) is a rare condition characterized by muscle weakness in the form of hyperthyroidism and hypokalemia. We present the case of a 38‐year‐old Hispanic male with PP that had been occurring over the course of 4 years. After several emergency department visits, the cause of his symptoms was still unknown. Initial laboratory testing revealed critical hypokalemia with associated electrocardiogram (ECG) changes. Further laboratory evaluation revealed hyperthyroidism, and the diagnosis of thyrotoxic PP was made. The patient received potassium supplementation with complete resolution of his symptoms and resolution of pathologic ECG changes. Our patient was started on propranolol and methimazole to treat his hyperthyroidism. Not well documented in previous reports, we stress the importance of using serial ECGs as an adjunct to patient improvement.